The impact of crises on the intellectual capital of companies in the food sector - Jakub Garncarz; Mateusz Mierzejewski (e-Finanse: Financial Internet Quarterly, 2019)
Both the financial crisis of the first decade of the 21st century, as well as the deterioration of trade relations between the European Union and the Russian Federation were events that significantly affected the functioning of the largest listed companies on the food market: on the one hand, aggravating the conditions of economic functioning, on the other hand creating a stimulus to seek new innovative solutions to help companies survive on the market. The aim of the work was to present the impact of crises on the intellectual capital of WIG-Food index companies, which is an indirect measure of innovation. The MV/BV and q-Tobin index were used for the study, as well as selected quantitative methods: multiple regression, Ward's method and seasonal additive decomposition. The results of the work indicate that the companies are divided into two groups, within which similar trends in shaping intellectual capital are observed. In addition, one of the groups clearly noticed the impact of the financial crisis and the introduction of an embargo on the shaping of intellectual capital.
Keywords: O34; G01; L66; 330; intellectual capital; agriculture; crisis; embargo; food industry